ANALISIS KINERJA BADAN AMIL ZAKAT NASIONAL KOTA TASIKMALAYA MENGGUNAKAN METODE BALANCED SCORECARD PERIODE TAHUN 2021-2022 - Fauzy Ridwan, Irwan; Sopiyawati Anggini Pratama (LPPM IAIT, 2023)
Building a trustworthy and professional image for a zakat management organization is a top priority in addressing the crisis of trust within the community. In this regard, zakat institutions need effective management of zakat, infaq, and alms that prioritize principles of trustworthiness, professionalism, accountability, and transparency to earn the full trust of the community. Therefore, institutions like the National Zakat Amil Agency (BAZNAS) must design effective strategic plans to fulfill their roles and functions.Furthermore, performance assessment or measurement is also a critical element in monitoring the institution's success. To enhance the performance of the Tasikmalaya City BAZNAS, a comprehensive assessment or measurement is required, such as a balanced scorecard. This allows for the evaluation of the zakat institution's performance and identifies areas needing improvement. The balanced scorecard comprises four perspectives: financial, customer, internal business processes, and growth and learning. It emphasizes essential aspects often overlooked in traditional performance measurements, including human resources, operational processes, systems used within the organization, and customer satisfaction, resulting in more accurate measurement outcomes. This research aims to measure the performance of BAZNAS Tasikmalaya City using the Balanced Scorecard framework. The analytical method employed is descriptive with a quantitative approach. In descriptive analysis, this research provides explanations in the form of words and sentences to describe the results of quantitative analysis and elucidate phenomena arising from the data obtained. The research findings indicate that Tasikmalaya City BAZNAS' performance is considered good from a financial perspective (score 1), relatively good from a customer perspective (score 0.7), not satisfactory from an internal business process perspective (score -0.5), and reasonably good from a growth and learning perspective (score 0.7).